2020
DOI: 10.5713/ajas.18.0925
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wilting and additives on fermentation quality and carbohydrate composition of mulberry silage

Abstract: Objective: The objective of this study was to investigate the effects of wilting and additives on the fermentation quality, structural and non-structural carbohydrate composition of mulberry silages. Methods: The selected lactic acid bacteria strains Lactobacillus plantarum 'LC279063' (L1), commercial inoculant Gaofuji (GF), and Trichoderma viride cellulase (CE) were used as additives for silage preparation. Silage treatments were designed as control (CK), L1, GF, or CE under three wilting rates, that is wilti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
6
13
0
1
Order By: Relevance
“…In addition, wilting and L. plantarum can reduce the content of AA and BA, which can improve palatability of the silage. Similar results have been reported by Zhang et al [ 23 ], who found wilting and L. plantarum decreased AA and BA contents of mulberry silage.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, wilting and L. plantarum can reduce the content of AA and BA, which can improve palatability of the silage. Similar results have been reported by Zhang et al [ 23 ], who found wilting and L. plantarum decreased AA and BA contents of mulberry silage.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, regardless of enriching lactic acid bacteria in fresh raw materials (Chen et al, 2017) or adding external lactic acid bacteria artificially during ensiling (Zhang et al, 2020), relative abundance or cultivable quantity of various species of microorganisms have been the principal consideration rather than metabolic functions. Thus, there might be some neglected effects from additives or environmental factors in the silage fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…2 Relative abundance of bacteria at the phylum level. M, pre-ensiled sample; CK, control (no addition); T, with addition of cellulase; 30, ensiled for 30 days; 60, ensiled for 60 days; the same as other groups; 1, 2, 3, triplicate per treatment addition of cellulase leads to a dramatic increase in the number of lactic acid bacteria and expands the effect of anaerobic fermentation [24]. On the other hand, alfalfa has been identified as having high antibacterial activity [25], which may inhibit the growth of microbes.…”
Section: Discussionmentioning
confidence: 99%